Religião, identidade e estigmatização: Agostinho e os pagãos na obra De Civitate Dei - Coelho, Fabiano de Souza (2011)
The city of Rome was sacked on August 24 th , 410 A.D. by the Visigoths under Alaric’s command. The attack lasted three days and three nights. This episode led pagans to argue about the new political and religious order then adopted in the Roman Empire – the tempora christiana. At that time, Augustine (354-430 A.D.), who was Bishop of the city of Hippo (north of the Roman Africa), was one of the most important figures of the dispute between Christians and Pagans, as well as one of the most remarkable characters in the History of the Christian Church and of mankind. The sack of Rome led Bishop Augustine of Hippo write his replies to Pagans – an apology to Christianity – throughout the XXII Books of the De Civitate Dei. This response was presented to the aristocratic pagans that defended the mos maiorum, especially those participating in the intellectual circle guided by Volusiano, consul of Carthage, and those who opposed to the spread of the new religious organization within the Roman Empire. Taking the piece The City of God as primary documentation, this research paper will present an analysis of Bishop Augustine of Hippo’s speech, which redefined the Christian identifying structure, and as a consequence, summarized the social process of pagans’ distinction and exclusion.